Using Islamic Videos to Increase the Writing Skills of the Senior High School Students - Dewi Yusmananda, Putri; Iksan, Muhammad (FOSTER: Journal of English Language Teaching, 2023)
The research aims to determine the effectiveness of Islamic Videos in increasing the students' writing skills and perceive the use of Islamic videos (History of Rasulullah). This research used Classroom Action Research (CAR); this study was located at Senior High School 1 Lasusua. The study was done on 28 September-02 November 2021. The research subject was XI IPA 2, and their total was 28. The instruments of this research were tests, observation techniques, and interviews. This research used two cycles in which every process had four steps: planning, implementing, observing, and reflecting. The researcher analyzed the observation qualitatively and then analyzed the test quantitatively. The students' mean score in cycle 1 was 74.46, while the mean score in cycle 2 was 80.21. it can be concluded that the Islamic video (history of Rasulullah) increased the students' ability to write narrative text students' learning outcomes. To overcome the lack of student mastery in writing narrative text, the researcher solved it in several ways: (1) the researcher applied an Islamic video (history of Rasulullah). (2) Doing exercise in every meeting. (3) Reviewing the current material in every meeting. Doing the action shows that students always made an improved learning activity and a vast understanding of the material. Besides that, the students felt enjoyed and fun during the learning process.